Performance management systems' stability: Unfolding the human factor – A case from the Italian public sector. Issue 3 (April 2018) - Maran, Laura; Bracci, Enrico; Inglis, Robert
Abstract: The aim of this study is to examine the institutional context during the emergence of New Public Management (NPM), which created pressure on public sector organizations to implement performance management systems (PMSs), such as the balanced scorecard (BSC). Drawing on Granlund's framework (2001) and Giddens' (1979) structuration theory, we engage insights from a longitudinal case study of an Italian local authority to show how managers exercise agency before the mandated implementation of the BSC. This analysis suggests a re-interpretation of Granlund's (2001) factors of inertia (human, institutional and economic) in terms of balance among the three factors, and inclusion of a historic and culturally specific perspective. The findings also encourage a broader consideration of the agency of managers in a public entity before the design and enhancement of a NPM tool.